Commonwealth Government records about Tasmania : research guide - Piggott, Michael, 1948-; National Archives of Australia ([Canberra, Australian Capital Territory] : National Archives of Australia, 2013)
"Michael Piggott identifies some broad enduring themes froim more than a century of interaction between Hobart and Canberra. This guide offers a sample of the vast resources of files, photos and other material available through the National Archives' website and its reading rooms. Where especially relevant, the guide also points to the collections of other archives such as the Tasmanian Archive and Heritage Office. It includes additional information to help researchers including those undertaking family history, academic and other scholarly investigations, local histories or compiling heritage material. The guide includes an A-Z section of micro stories. They show that more Tasmanian stories can be found using Commonwealth records that have been overlooked for too long or perviously unknown."--Back cover.
At foot of title: "National Archives of Australia".
Includes bibliographical references and index.
Also available online. On 21/3/2014 freely available from the website of the National Archives of Australia at: http://www.naa.gov.au/collection/publications/guides.
Keywords: National Archives of Australia -- Catalogs; Public records -- Tasmania -- Bibliography -- Catalogs; Public records -- Australia -- Bibliography -- Catalogs; Tasmania -- History -- Sources -- Bibliography -- Catalogs; Tasmania; Archives; History; Government information; Federal state relations; National Archives of Australia; Reference works; Australian